2021
DOI: 10.3390/v13091880
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Damage by SARS-CoV-2: Emerging Mechanisms and Therapies

Abstract: Evidence is emerging that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can infect various organs of the body, including cardiomyocytes and cardiac endothelial cells in the heart. This review focuses on the effects of SARS-CoV-2 in the heart after direct infection that can lead to myocarditis and an outline of potential treatment options. The main points are: (1) Viral entry: SARS-CoV-2 uses specific receptors and proteases for docking and priming in cardiac cells. Thus, different receptors or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 184 publications
1
17
0
Order By: Relevance
“…ACE2 (angiotensin-converting enzyme 2) receptor attaches to cell surfaces in the lung, blood vessels, heart, kidney, and intestines [ 28 ]. SRA-CoV-2 can infect cardiomyocytes and cardiac endothelial cells in the heart [ 29 , 30 ]. This study found that cardiac index (D-dimer, LDH, TNT, and BNP) in severe/critical patients was significantly higher than that of mild/moderate patients, and cardiovascular was a significant risk factor for progressing to severe infection in univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…ACE2 (angiotensin-converting enzyme 2) receptor attaches to cell surfaces in the lung, blood vessels, heart, kidney, and intestines [ 28 ]. SRA-CoV-2 can infect cardiomyocytes and cardiac endothelial cells in the heart [ 29 , 30 ]. This study found that cardiac index (D-dimer, LDH, TNT, and BNP) in severe/critical patients was significantly higher than that of mild/moderate patients, and cardiovascular was a significant risk factor for progressing to severe infection in univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of cardiac damage in COVID‐19 patients has been reported in several previous studies 19–21 . Myocardial inflammation has been reported in 60% of patients with recent (<3 months) COVID‐19 infection, regardless of pre‐existing conditions 22 .…”
Section: Discussionmentioning
confidence: 73%
“…Evidence of cardiac damage in COVID‐19 patients has been reported in several previous studies. 19 , 20 , 21 Myocardial inflammation has been reported in 60% of patients with recent (<3 months) COVID‐19 infection, regardless of pre‐existing conditions. 22 Myocardial inflammation triggers a progressive fibrotic remodeling of the heart, which will lead to hardening of the cardiac tissue and altered cardiac relaxation.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was proven to be a multiple organ disease also affecting the heart[ 2 , 3 ]. Studies revealed that cases of critically ill COVID-19 patients had cardiovascular complications such as myocardial damage, venous thromboembolic events, and acute coronary syndromes[ 4 ]. The presence of underlying cardiovascular comorbidities in COVID-19 patients is associated with severe disease and poor prognosis including increased risk of onset of cardiovascular complications, increased progression of underlying cardiovascular disease and risk of increased mortality both in general population as well as in diagnosed patients[ 5 ].…”
Section: Introductionmentioning
confidence: 99%